Modeling of a New High Voltage Power Supplyfor Microwave Generators with Three Magnetrons - Bahani Boubker; A. Bouzit; M. Chraygane; M. Ferfra; N. El Ghazal; A. Belhaiba (International Journal of Electrical and Computer Engineering (IJECE), 2013)
This original work treats the modeling of a new type of HV power supply with several magnetrons (treated case   N=3 magnetrons).The design of this new power supply uses a new single-phase high voltage transformer with magnetic shunts supplying three doublers voltage cells, each one composed of a capacitor and a diode. Each cell supplies in its turn one magnetron. The π equivalent model of the transformer is developed taking account the saturation phenomena and the stabilization process of each magnetron current. The model of the transformer is based on the determination of the analytical expressions of the non linear inductances that can be stored from the fitting of the magnetization curve B (H) of material used. The resulting model will be implemented under Matlab-Simulink code. The simulation results are in good agreement with the experimental measurement for one magnetron, thus provides, relative to the current device, gainsof volume, weight and cost of all power supply with respecting the conditions recommended by the constructor of magnetron current: Ipeak<1.2 A, Imean≈ 300 mA.DOI:http://dx.doi.org/10.11591/ijece.v3i2.2238